Functional outcome after endoscopic assisted release of the ulnar nerve for cubital tunnel syndrome: mid-to-long term results - Spies, Christian; Schäfer, Melanie; Langer, Martin Franz; Bruckner, Thomas; Müller, Lars Peter; Unglaub, Frank (International orthopaedics, 2018)
AIM OF THE STUDY: The aim of the study was to investigate functional and patient-rated outcome parameters after endoscopic assisted release of the ulnar nerve for cubital tunnel syndrome. - METHODS: One hundred of 204 consecutive patients between 2006 and 2011 met the inclusion/exclusion criteria. Fifty-one of these patients were recruited and evaluated clinically and by questionnaire testing retrospectively after a mean follow-up of 82 months (range: 60-116). - RESULTS: Neurological parameters (two-point-discrimination, application of Semmes-Weinstein monofilaments, Tinel's test), grip, and three-point pinch strength were not significantly different from the contralateral extremity at the time of examination, whereas key pinch strength was significantly weaker. Mean Disabilities of the Arm, Shoulder, and Hand score was 20.82. Patients' overall opinion was good/excellent for 78% of the study population. - DISCUSSION: The examined surgical procedure proved to be as efficacious as open in-situ decompression regarding functional outcome with fewer post-operative complications. Regarding the results it might be postulated that grip strength and three-point pinch strength determination is not necessarily relevant for ulnar nerve evaluation. - CONCLUSION: Endoscopic assisted release of the ulnar nerve is a reliable and safe treatment option for cubital tunnel syndrome with satisfactory mid-to-long term functional and patient-rated outcomes.